Conservation Genomics of the Threatened Western Spadefoot, Spea hammondii, in Urbanized Southern California. (29th January 2021) - Neal, Kevin M; Fisher, Robert N; Mitrovich, Milan J; Shaffer, H Bradley
Abstract: Populations of the western spadefoot ( Spea hammondii ) in southern California occur in one of the most urbanized and fragmented landscapes on the planet and have lost up to 80% of their native habitat. Orange County is one of the last strongholds for this pond-breeding amphibian in the region, and ongoing restoration efforts targeting S. hammondii have involved habitat protection and the construction of artificial breeding ponds. These efforts have successfully increased breeding activity, but genetic characterization of the populations, including estimates of effective population size and admixture between the gene pools of constructed artificial and natural ponds, has never been undertaken. Using thousands of genome-wide single-nucleotide polymorphisms, we characterized the population structure, genetic diversity, and genetic connectivity of spadefoots in Orange County to guide ongoing and future management efforts. We identified at least 2, and possibly 3 major genetic clusters, with additional substructure within clusters indicating that individual ponds are often genetically distinct. Estimates of landscape resistance suggest that ponds on either side of the Los Angeles Basin were likely interconnected historically, but intense urban development has rendered them essentially isolated, and the resulting risk of interruption to natural metapopulation dynamics appears to be high. Resistance surfaces show that the existing artificial ponds were well-placed and connected to natural populations by low-resistance corridors. Toad samples from all ponds (natural and artificial) returned extremely low estimates of effective population size, possibly due to a bottleneck caused by a recent multi-year drought. Management efforts should focus on maintaining gene flow among natural and artificial ponds by both assisted migration and construction of new ponds to bolster the existing pond network in the region.